Bayesian estimation of generalized half logistic type II doubly censored data - Azimi, Reza (International Journal of Scientific World, 2013)
This study considers the estimation problem for the parameter and reliability function of generalized half logistic distribution under Type II Doubly censored data. We use the Bayesian procedures (under asymmetric loss functions (Linex and general entropy) and symmetric loss function (squared-error)) to obtain the estimators of parameter and reliability function of generalized half logistic distribution .